PENGARUH PENGUNAAN MEDIA GAMIFIKASI TERHADAP KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR NEGERI CIKOKOL 01 KOTA TANGERANG - Nur Ajharapip; Pratiwi Kartika Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is that the researcher found that the independence of student learning in the school was still low because. To determine the effect of the use of gamification media on student learning independence is the purpose of this study. The quantitative quasi-experimental method was used in this study. The sample was students of grades IV A and B, 31 students each, for the Pretest-Posttest Nonequivalent Comparison Group research design. This study collected data through tests, interviews, and documentation. The results of the Gamification Media study have a significant effect on increasing student learning independence in grade IV of elementary school. The results of hypothesis testing with the t-test at the end of learning (posttest) in the control class and the experimental class obtained tcount = 3.648 with a significance level of 95% (∞ = 0.05) obtained t-table = 2.000 because 3.648> 2.000 (t-count> t-table) then Ho is rejected. These results indicate that Gamification Media is more effective in significantly increasing student learning independence.